Congenital Internal Auditory Canal Stenosis - Nathaniel Yang (Philippine Journal of Otolaryngology Head and Neck Surgery)
A 3-year-old boy underwent evaluation for possible cochlear implantation. He had failed a neonatal otoacoustic emission (OAE) hearing screen. A combined auditory brainstem response/auditory steady-state response (ABR/ASSR) test battery confirmed the presence of a severe hearing loss on the right and a profound hearing loss on the left. No Joint Committee on Infant Hearing (JCIH) risk factors for early childhood hearing loss1 were identified. Rehabilitation via hearing aid amplification and auditory-verbal speech therapy was unsuccessful. Computerized tomographic (CT) imaging of the temporal bone was performed to identify the presence of any inner ear abnormalities. No abnormalities of the cochlea, vestibule and semicircular canals on both sides were identified by the radiologist. The internal auditory canals were described as “fairly symmetrical without widening”, and the study was officially reported as an “unremarkable study of the temporal bones”.